A Corpus-based Analysis of The use of Discourse Markers in Master Two (linguistics) dissertations - Zouza Racha, Guerari Asma (UNIVERSITY OF MOHAMED BOUDIAF, 2022)
Abstract Writing a dissertation can be one of the most difficult challenges in the academic context. The use of cohesive devices and particularly discourse markers can improve the quality of writing and facilitate the interpretation of ideas by the readers. The current study aims to investigate the use of discourse markers in the discussion sections of master two linguistics students in the department of English (M'sila University) and to identify the dominant classes of these linguistic items to be able to evaluate the accuracy of their use. This research is a corpus-based study that analyses 30 discussion sections both quantitatively and qualitatively. It adopts Fraser's (2009) classification of discourse markers. Data was collected through the use of a concordance tool ( AntConc 3.2.4.2020). The results show that the three classes are used and the class of elaborative discourse markers is the dominant class while the class of inferential discourse markers is the least used one. The qualitative analysis reveal that elaborative discourse markers are used more correctly than the other classes and contrastive discourse markers received the least percentage of correct use. Moreover, issues related to the overuse, the underuse, the use of few types, and the misuse characterised discourse markers use. This study raises awareness of students to the importance of these lexical items in enhancing the quality of their written productions. This research recommends conducting a detailed study of each class of DMs or of individual DMs to figure out the problems that face students while using these lexical items
Keywords: Keywords: discourse markers, academic writing, coherence, corpus, master dissertations, master two students